Ajaran budaya masyarakat Aceh dan implikasinya terhadap kerukunan antarumat beragama di Peunayong - Dira Ranisa, Dira; Mulyazir; Rifai, Akhmad; Ranisa, Dira; Rifai , Akhmad (Fakultas Adab dan Humaniora UIN Raden Fatah, 2024)
Aceh is often considered one of the most intolerant regions in Indonesia, but the existence of Peunayong as a Chinatown in Banda Aceh City shows otherwise. Although Aceh implements Islamic Shari'a, the province does not limit or prevent people of other religions from worshiping, expressing, and preserving their culture. The existence of the Chinese community in Aceh and their freedom and comfort in worship and activities are proof of tolerance in this area. This research aims to analyze and explore the harmonious and mutually supportive relationship in the area and identify the factors that support its sustainability until today. To answer this question, the researcher used a descriptive-analytical method by focusing on library research to find research data. The findings of this study show that cultural teachings are one of the main reasons for the harmony in Peunayong. Therefore, these findings need to be used as a basis for further research in an effort to maintain and improve interfaith harmony in Peunayong.